Nano Spray TRISWHEAT (Teripang Super Wound Healing Agent) Penyembuh Luka Diabetes Mellitus yang Terinfeksi Bakteri MRSA (Methicillin Resistant Staphylococcus aureus) dengan Ekstrak Teripang - Nada Hanifah; Yusuf Farid Achmad; Mellya Permatasari; Marista Kurniati; Ditya Tiwi Syafira; Siti Isrina Oktavia Salasia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Sea Cucumber (Stichopus sp) belongs to Holothuroidea family. Sea Cucumber has lot of uses in the medicine sector, such as: for wound healing, anti-biotic, anti-bacteria, anti-tumor, and anti-coagulation. Diabetes mellitus is a disease characterized by high blood sugar levels with metabolic disorders. This disease can cause wounds called gangrene This research has purpose to prove the influence of giving nano spray of sea cucumber extract within 14 days. In the in vitro examination found 40% concentration of sea cucumber extract which is effective to resist the growth of Methicillin Resistant Staphylococcus aureus bacteria and examined to wistar mouse which are already diabetic inducted with Streptozotocin (STZ) and hurt with punch biopsy with the diameter of 0,8 cm on its back and the wound is infected with bacteria which is intradermal injected. Divided into 3 groups : (K-) no medical treatment, nano spray of sea cucumber extract (T), Nano spray penicillin (K+) to wistar mouse towards the speed of diabetic mellitus wound healing which is infected by Methicillin Resistant Staphylococcus aureus bacteria. Parameter used to measure the rate of wound healing is wound size and hitopathology examination.After it’s regularly given the medicine, the result of nano spray sea cucumber extract 40 % concetration category treatment on wound healing process the diameter of wound on the 3rd day 0.8 cm , on the 7th day 0.4 cm and on the 14th day wound fully recover according to macros (wound size) and histopathology examination shows faster and better healing compared to treatment category of nano spray penicillin and control marked by score cell and lymphocyte in a small quantity.